PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI YAYASAN TA’DIBUL UMMAH BOGOR - wicaksono, Widhi; Sudarso, Aden Prawiro; Suyatin, Suyatin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine the effect of organizational culture and motivation on employee performance at Ta’dibul Ummah Foundation Bogor. The method used in this study is a quantitative method with a saturated sample of 56 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results showed that organizational culture had a positive and significant effect on employee performance with the value of the regression equation Y = 6.725 + 0.839X1, The coefficient of determination was 33.2%. Hypothesis test obtained value of t count > t table or (5,176 > 2,004). Thus H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between organizational culture on employee performance. Motivation has a positive and significant effect on employee performance with the value of the regression equation Y = 15,406 + 0.658X2. The value of the coefficient of determination is 33.7%. Hypothesis test obtained value of t count > t table or (5,244> 2,004). Thus H0 is rejected and H2 is accepted, meaning that there is a positive and significant influence between motivation on employee performance. Organizational culture and motivation have a positive and significant effect on employee performance with the value of the regression equation Y = 3.176 + 0.509X1 + 0.411X2. The coefficient of determination is 41.2% while the remaining 58.8% is influenced by other factors. Hypothesis testing obtained Fcount > Ftable or (18,549 > 3.172 ) Thus H0 is rejected and H3 is accepted, meaning that there is a simultaneous positive and significant influence between organizational culture and motivation on the performance of the employees of the Ta’dibul Ummah Foundation Bogor.